Corrigendum: Immunomodulatory effects of a probiotic combination treatment to improve the survival of Pacific oyster ( - Hesser, Jennifer; Mueller, Ryan; Langdon, Chris; Schubiger, Carla (Frontiers in Immunology, 2024)
[This corrects the article DOI: 10.3389/fimmu.2024.1380089.].